Improving cardiology fellow education of right heart catheterization using a simulation based curriculum. Issue 3 (30th June 2020) - Davidson, Laura J.; Chow, Kimberly Y.; Jivan, Arif; Prenner, Stuart B.; Cohen, Elaine R.; Schimmel, Daniel R.; McGaghie, William C.; Barsuk, Jeffrey H.; Wayne, Diane B.; Sweis, Ranya N.
Abstract: Background: Medical procedures are traditionally taught informally at patients' bedside through observation and practice using the adage "see one, do one, teach one." This lack of formalized training can cause trainees to be unprepared to perform procedures independently. Simulation based education (SBE) increases competence, reduces complications, and decreases costs. We developed, implemented, and evaluated the efficacy of a right heart catheterization (RHC) SBE curriculum. Methods: The RHC curriculum consisted of a pretest, video didactics, deliberate practice, and a posttest. Pre‐and posttest skills examinations consisted of a dichotomous 43‐item checklist on RHC skills and a 14‐item hemodynamic waveform quiz. We enrolled two groups of fellows: 6 first‐year, novice cardiology fellows at Northwestern University in their first month of training, and 11 second‐ and third‐year fellows who had completed traditional required, level I training in RHC. We trained the first‐year fellows at the beginning of the 2018–2019 year using the SBE curriculum and compared them to the traditionally‐trained cardiology fellows who did not complete SBE. Results: The SBE‐trained fellows significantly improved RHC skills, hemodynamic knowledge, and confidence from pre‐ to posttesting. SBE‐trained fellows performed similarly to traditionally‐trained fellows on simulated RHC skills checklists (88.4% correct vs. 89.2%, p = .84), hemodynamic quizzes (94.0% correct vs. 86.4%, p = .12), and confidence (79.4 vs. 85.9 out of 100, p = .15) despite less clinical experience. Conclusions: A SBE curriculum for RHC allowed novice cardiology fellows to achieve level I skills and knowledge at the beginning of fellowship and can train cardiology fellows before patient contact.